Predictive value of the Delphian lymph node in cervical lymph node metastasis of papillary thyroid carcinoma. Issue 7 (July 2021) - Yan, Yunfei; Wang, Yu; Liu, Na; Duan, Yuansheng; Chen, Xiaohan; Ye, Beibei; Yang, Rong; Zhang, Wenchao; Wang, Xudong
Abstract: Introduction: Delphian lymph node metastasis (DLNM) has proven to be a risk factor for a poor prognosis in head and neck malignancies. This study aimed to reveal the clinical features and evaluate the predictive value of the Delphian lymph node (DLN) in papillary thyroid carcinoma (PTC) to guide the extent of surgery. Methods: Tianjin Medical University Cancer Institute and Hospital pathology database was reviewed from 2017 to 2020, and 516 PTC patients with DLN detection were enrolled. Retrospective analysis was performed, while multivariate analysis was performed to identify the risk factors for DLNM. Results: Among the 516 PTC patients with DLN detection, the DLN metastasis rate was 25.39% (131/516). Tumor size >1 cm, location in the upper 1/3, central lymph node metastasis (CLNM), lateral lymph node metastasis (LLNM) and lymphovascular invasion were independent risk factors for DLNM. Patients with DLNM had a higher incidence of ipsilateral CLNM, contralateral CLNM (CCLNM) and LLNM, and larger numbers and size of metastatic CLNs than those without DLNM. The incidence of CLNM among cN0 patients with DLNM was higher than that among those without DLNM. The incidence of CCLNM among unilateral cN + patients with DLNM was similarly higher than that among patients without DLNM. Conclusions: DLNM indicates a high likelihood and large number of cervical lymph nodes metastases in PTC patients. Surgeons are strongly recommended to detect DLN status during operation by means of frozen pathology, so as to evaluate the possibility of cervical nodal metastasis and decide the appropriate extent of surgery.